Evolution of United States Budgeting: Changing Fiscal and Financial Concepts. - Gordon, Teresa P.; Moriarity, Shane R. (The Accounting Review, 1990)
Reviews the book `Evolution of United States Budgeting: Changing Fiscal and Financial Concepts,' by Annette E. Meyer.